The Juridical Review on the Misappropriation of Foundation Funds is Reviewed Based on Law of the Republic of Indonesia Number 8 of 2010 Concerning the Prevention and Eradication of Money Laundering - Ahmad Bukhori Siregar; Kusno Kusno; Ahmad Ansyari Siregar (International Journal Labs, 2023)
This study aims to find out and analyze the criminal act of embezzlement in educational foundations. As well as knowing and analyzing the factors of embezzlement in the foundation. This research belongs to the normative type of research. So it can be seen that it can be concluded that the Criminal Linkage can clearly be seen in Article 2 paragraph (1) of Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering. Predicate crime is a crime that triggers (source) the occurrence of money laundering crimes, so the handling of money laundering cases has an important meaning for the return of state assets related to the eradication of corruption.